Symposium 6: Staff Development And E-Tutors Training - Banks, Sheena; Denis, Brigitte; Fors, Uno; Pirotte, Sébastien (Proceedings of the International Conference on Networked Learning, 2004)
This paper considers the rationale for the training and staff development of e-tutors. We then examine how this is implemented in practice through the presentation of case studies from three European universities. Finally we analyse the differences and similarities of these case studies to exemplify some principles for training models and guidelines for training of e-tutors. We conclude that although it is possible to identify these principles of good practice, there is great flexibility and diversity of methods and approaches in the training and staff development of e-tutors.